Step one - Steps; Zomba Records (United Kingdom : Zomba Records, 1998)
Contains four pop mixed tracks.
CD 1 : Last Thing On My Mind (radio edit) -- Last Thing On My Mind (wip't up in the disco mix) -- Last Thing On My Mind (instrumental) -- 5,6,7,8 (radio edit).
Koleksi Khas Wiramanja.
Group members : Claire Richards, Ian'H' Watkins, Lisa Scott-Lee, Lee Latchford-evans, Faye Tozer.
Title from container.
Keywords: Disco music; Dance music